2023
DOI: 10.3389/fpls.2022.1071511
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of methane uptake by precipitation pulses and long-term nitrogen addition in a semi-arid meadow steppe in northeast China

Abstract: In the context of global change, the frequency of precipitation pulses is expected to decrease while nitrogen (N) addition is expected to increase, which will have a crucial effect on soil C cycling processes as well as methane (CH4) fluxes. The interactive effects of precipitation pulses and N addition on ecosystem CH4 fluxes, however, remain largely unknown in grassland. In this study, a series of precipitation pulses (0, 5, 10, 20, and 50 mm) and long-term N addition (0 and 10 g N m-2 yr-1, 10 years) was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…The study area has a temperate semi-arid continental climate, with a mean annual air temperature of 6.4°C (Meng et al, 2021a), average annual precipitation of 445 mm, and over 80% of precipitation occurring during the growing season (from May to September) (Li et al, 2019a). The zonal soil at the study site is classified as Salic Solonetz (World Reference Base for Soil Resources) or an Aqui-Alkalic Halosol (Chinese soil classification) with a pH of 8.0-9.0 (Gao et al, 2023). Soil texture (28.9% clay, 40.1% silt, and 31.0% sand) corresponds to clay loam soil (Shi et al, 2021).…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…The study area has a temperate semi-arid continental climate, with a mean annual air temperature of 6.4°C (Meng et al, 2021a), average annual precipitation of 445 mm, and over 80% of precipitation occurring during the growing season (from May to September) (Li et al, 2019a). The zonal soil at the study site is classified as Salic Solonetz (World Reference Base for Soil Resources) or an Aqui-Alkalic Halosol (Chinese soil classification) with a pH of 8.0-9.0 (Gao et al, 2023). Soil texture (28.9% clay, 40.1% silt, and 31.0% sand) corresponds to clay loam soil (Shi et al, 2021).…”
Section: Study Sitementioning
confidence: 99%
“…Continued global warming has altered worldwide precipitation patterns, including precipitation amount, precipitation intensity, precipitation interval, and precipitation timing (Bodelier, 2011;Fay et al, 2015;IPCC, 2021;Gao et al, 2023). Previous studies have shown that changes in the precipitation amount and frequency are likely to alter soil wet and dry cycles, which in turn affects key ecosystem functions, such as primary productivity (Nielsen and Ball, 2015;Wu et al, 2021;Du et al, 2023).…”
Section: Introductionmentioning
confidence: 99%